Every Child Needs Special Attention: Understanding Individual Variations Using Reading Track Table (RTT) - Mondal, Atanu (Journal of Information and Knowledge, 2026)
The study attempts to identify individual variation in reading among children and suggests that each and every child needs special attention. A total sample of 26 children of Kolkata district aged 12 years and a sample of 26 parents (one parent of each child) were considered. The conclusions were drawn by comparing the results of pre and post training test using the Reading Track Table. It was found that every child varies when tested on criteria, viz., pronunciation, reading time, understanding meaning and response time of the text. The study revealed that each child performed better in the posttraining test. The study claimed that, as every child is unique, special attention should be given to each to improve reading habits.